Prekursor MJO-Crossing (MJO-C) dan MJO-Blocking (MJO-B) di Benua Maritim Berdasarkan Transpor Kelembapan - Fahim, Akhmad; Trilaksono, Nurjanna Joko (Pusat Penelitian dan Pengembangan BMKG, 2023)
Research on MJO propagation that is blocked when crossing the Maritime Continent (MC) is a complex problem. This research aims to determine the precursors of MJO-Crossing (MJO-C) and MJO-Blocking (MJO-B) based on moisture transport analysis. Hovmöller analysis on MJO-C and MJO-B is performed using precipitation data retrieved from the TRMM satellite (3B42v7) in the ONDJFM period 1998-2015 to characterize the propagation of MJO-C and MJO-B. The difference between MJO-C and MJO-B propagation is further investigated using specific humidity and horizontal wind data from ERA-Interim ECMWF to examine the moisture source and vertical structure of specific humidity in MJO-C and MJO-B. Additionally, we conducted wind divergence analysis at 700hPa to identify the characteristics of wind patterns in MJO-C and MJO-B events. Our investigation revealed that during the precursor period (day -15 to -5) or before MJO arrived at the Maritim Continent, there was a weakening of moisture supply in MJO-B events due to the existence of a westward-propagating dry anomaly. This dry anomaly mixed with the moist anomaly of MJO convection could reduce the intensity of moisture and dissipate MJO convection. The westward-propagating dry anomaly indicates the influence of Equatorial Rossby (ER) waves, which can inhibit MJO propagation across the Maritime Continent.